PENERAPAN PASAL 2 AYAT (2) UNDANG-UNDANG NOMOR 20 TAHUN 2001 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 31 TAHUN 1999 TENTANG PEMBERANTASAN TINDAK PIDANA KORUPSI TERHADAP PELAKU TINDAK PIDANA KORUPSI BANTUAN BENCANA - Dobi Umbara; Evi Deliana; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In essence, corruption can damage the structure of government, and become amajor obstacle to the running of government and development in general. One of thecauses of non-optimal development is the practice of corruption, because corruptionaffects the investment climate, economic growth and increases people's income. InIndonesia, the perpetrators of criminal acts of corruption at a certain period can besentenced to death by a judge. However, none of the perpetrators of the CorruptionCrime of disaster relief funds have been sentenced to a death penalty in accordancewith the Corruption Crime Act, in the conditions of the Covid-19 Pandemic, they havefulfilled the elements under certain conditions. The objectives of this research are:first, to find out the application of Article 2 paragraph (2) of Law Number 20 of 2001concerning amendments to Law Number 31 of 1999 concerning the Crime ofCorruption against the perpetrators of Corruption Crime of Disaster Assistance,second, to know that the judge's consideration is not applied Article 2 paragraph (2)of Law Number 20 of 2001 concerning amendments to Law Number 31 of 1999concerning criminal acts of corruption against perpetrators of corruption in disasterassistance.The author conducts research using normative juridical methods or literaturestudies in order to obtain secondary data through documentary studies, namely bystudying and analyzing comparatively deductively against laws and regulations withtheories that have a relationship with the problems studied.From the results of the research, there are two main problems: first, how is theapplication of Article 2 paragraph (2) of Law Number 20 of 2001 concerningamendments to Law Number 31 of 1999 concerning Corruption Crimes againstCorruption Criminal Act perpetrators of Disaster Assistance, second, 2 What is thejudge's consideration not to apply Article 2 paragraph (2) of Law Number 20 of 2001concerning amendments to Law Number 31 of 1999 concerning criminal acts ofcorruption against perpetrators of corruption in disaster assistance. The author'ssuggestion from the results of this study, it is hoped that the judge can implement theapplicable Constitution, which has regulated the death penalty, which can be imposedat a certain time, in which case the Covid19 pandemic conditions have met theelements of certain conditions. It is hoped that the Judge in considering a decision inaccordance with the crime committed so that justice always exists in this country.Keywords: Corruption of Covid19 Pandemic Aid Funds